Patient Satisfaction with Private Community Pharmacies versus Pharmacies in Primary Health Care Centers in Saudi Arabia - Ali M. Alzahrani; Abdulrhman A. Alzhrani; Holly C. Felix; Khulud K. Alharbi; Muhammad Waseem Shahzad; Turky J. Arbaein; Sarah S. Monshi (Saudi Pharmaceutical Journal, 2024)
Introduction: Saudi Arabia has begun reforming its government-run health care system to increase efficiency and reduce costs. One effort is the adoption of an electronic prescribing system (Wasfaty) and outsourcing pharmaceutical services from government-run clinics to community pharmacies (CP). This study aims to compare satisfaction with pharmaceutical services offered in the two systems. Materials and methods: This cross-sectional observational study used existing survey data collected from patients (≥15 years of age) visiting government primary health care centers from January 2022 to June 2022. Satisfaction with three pharmaceutical services (availability of medications, pharmacist’s explanation of the prescription, and waiting time to get medications) were the main outcomes. Results: The study comprised 91,317 participants, 74.06 % of them were CP/Wasfaty users. CP/Wasfaty patients had lower odds of satisfaction with the three pharmaceutical services: availability of medications (OR = 0.49, 95 % CI = 0.47–0.51), pharmacists’ explanation of prescription (OR = 0.55, 95 % CI = 0.53–0.58), and waiting time to get medications (OR = 0.81, 95 % CI = 0.75–0.88). Additional findings showed variations in satisfaction levels based on demographic factors and clinic types. Conclusions: The significant differences observed in satisfaction levels based on demographic characteristics and type of clinics visited emphasize the importance of tailoring pharmaceutical services to meet the specific needs and expectations of different patient populations.